2013
DOI: 10.1136/bmjopen-2013-004023
|View full text |Cite
|
Sign up to set email alerts
|

Improving the identification of people with dementia in primary care: evaluation of the impact of primary care dementia coding guidance on identified prevalence

Abstract: ObjectiveImproving dementia care is a policy priority nationally and internationally; there is a ‘diagnosis gap’ with less than half of the cases of dementia ever diagnosed. The English Health Department's Quality and Outcomes Framework (QOF) encourages primary care recognition and recording of dementia. The codes for dementia are complex with the possibility of underidentification through miscoding. We developed guidance on coding of dementia; we report the impact of applying this to ‘clean up’ dementia codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…Rates of clinically diagnosed dementia are, as expected, lower than rates recorded in field-based studies based on case finding [1618], because some people with early dementia found in the case finding studies may not have been clinically diagnosed and thus would not have been recorded as having dementia in primary care data. Those diagnosed with dementia in primary care would not necessarily be admitted to hospital, and not all those admitted would have had dementia coded in their hospital records.…”
Section: Discussionsupporting
confidence: 57%
“…Rates of clinically diagnosed dementia are, as expected, lower than rates recorded in field-based studies based on case finding [1618], because some people with early dementia found in the case finding studies may not have been clinically diagnosed and thus would not have been recorded as having dementia in primary care data. Those diagnosed with dementia in primary care would not necessarily be admitted to hospital, and not all those admitted would have had dementia coded in their hospital records.…”
Section: Discussionsupporting
confidence: 57%
“…(20) A common element of health strategies to improve the quality of care of people with dementia is that diagnosis should be "early" or "timely". (21) In the Surrey Downs area, the diagnosis rate was 43% at the beginning of the study. an abnormal clock drawing test), and a score of more than 9 in the FAQ.…”
Section: Problemmentioning
confidence: 96%
“…The potential for these and other unknown structural factors to have an impact on our results cannot be ruled out. Fourth, data coding in clinical systems for dementia is variable and in some cases quite poor (Russell et al, 2013). Our study analyses the number of patients who have a recorded diagnosis of dementia on GP electronic patient records.…”
Section: Discussionmentioning
confidence: 99%